Towards ‘virtual’ corporate governance: an analysis of the legal framework governing virtual shareholder meetings in Kenya - Gathua, N. W. (Strathmore University, 2025)
The COVID-19 pandemic caused substantial transformations in traditional corporate governance practices worldwide, notably in the conduct and execution of company meetings. As a result of travel restrictions and prohibitions on physical gatherings, commonly known as lockdowns, companies faced the challenge of meeting statutory requirements within a legal framework that had not envisaged these far-reaching effects of the pandemic. The main legislation in Kenya governing companies, the Companies Act 2015, did not provide for virtual meetings. Various legal interventions were thus implemented to address the altered circumstances. With the pandemic officially over, this study sought to critically assess the adequacy of the current legal framework regulating virtual shareholder meetings. This is important as corporations have continued to hold virtual meetings even after the lifting of lockdowns and the resumption of in-person gatherings. Anchored on the agency theory, this doctrinal legal research examined the existing legislative framework with regard to virtual shareholder meetings and assessed the extent to which they ensure the effective exercise of shareholders’ rights during these meetings. The study also interrogated the legal and regulatory framework in Australia to determine if there are any lessons Kenya can borrow. The study established that shareholder meetings are a fundamental component of corporate governance, facilitating the core principles of transparency, accountability and fairness. The study further found that the COVID-19 pandemic accelerated the adoption of virtual shareholder meetings, enhancing accessibility while also posing challenges such as technological barriers and reduced accountability. The findings of the study highlight the shortcomings in the legal framework governing virtual shareholders’ meetings in Kenya. Based on the findings, the study recommends that the Companies Act should be amended to explicitly mandate that all shareholders attending virtual meetings be provided with a reasonable opportunity to participate. Additionally, the Act should provide clear guidelines on the scope and implementation of this requirement. These amendments would strengthen Kenya’s corporate governance framework by ensuring that virtual meetings uphold the core corporate governance principles. Key words: corporate governance, COVID-19, virtual meetings, shareholders rights.
Full - text thesis